Watsuji's topology of the self. Issue 3 (2nd July 2016) - Johnson, David W.
ABSTRACT: This essay critically develops Watsuji's nondual ontology of the self through the lens of 'topological' thought. Through close description of the embeddedness of the self in, and its emergence from, an intersubjective space which, in turn, is rooted in a particular place, Watsuji shows that the self is constituted by its relational contact with others, on the one hand, and by its immersion in a wider geo-cultural environment, on the other. Yet Watsuji himself had difficulty in smoothly bringing together and integrating these themes. By showing how these domains work together to constitute the self, we bring into view the unity at the ground of Watsuji's thought. Foremost among the difficulties in this account of the self is the question of how transcendence, the distance and difference that makes possible freedom and individuation, can be convincingly accounted for if the self is so completely identified with its insertion into social and natural structures. Beyond problems such as these, however, Watsuji's topology has important implications for key ideas in Heidegger's philosophy; it also suggests a new approach to an important problem in environmental ethics.